Sustainability of drying technologies: system analysis - Martynenko, Author Alex; Alves Vieira, Gustavo Nakamura [UNESP] (Royal Society of Chemistry (RSC), 2023)
Sustainability is a multi-dimensional indicator of the impact of current human activities on future generations. The concept of sustainability could be extended to food drying, reflecting the impact of current drying technologies on energy and resource use, as well as social and food security. The objective of this review is a sustainability assessment of drying, based on the so-called 4E system analysis considering energy, exergy, environmental and economic aspects. For energy analysis, instead of the ambiguous term “efficiency”, it is proposed to use specific energy consumption as a measure of the energy efficiency of drying. For exergy analysis, it is proposed to use specific exergy consumption as a measure of the efficiency of non-renewable resource usage. Both metrics, expressed in kilojoules per kg of extracted water, are good indicators of the sustainability of the drying process and their minimization is the objective of future research in drying technologies. The environmental impact of drying is evaluated as a potential carbon footprint and associated carbon tax rate. Economic analysis characterizes the sustainability of drying technology with the payback period and net present value, which are specific to the dried material. The insight into the effect of drying on the social aspects of sustainability, i.e. malnutrition and food insecurity is also presented. All aspects of sustainability are linked to each, showing how drying processes/technologies can contribute to a more sustainable world.